The operationalisation of the R&D assessment framework in Magneti Marelli Serbia - Pesic, Aleksandar Budimir; Pesic, Duska Petar; Apostolovic, Dejan (Serbian Journal of Management, 2016)
This paper has twofold purpose. Firstly, an assessment method aimed to evaluate R&D strategic performance indicators is introduced. The proposed framework is based on fuzzy set theory which represents an adequate tool for quantitatively describing the vague and ambiguous nature of the R&D function. The second purpose of the paper is to analyze relevant R&D performance indicators in Magneti Marelli S.p.A. Serbia, a leading supplier in Serbian automotive industry. Specific findings of this empirical analysis are discussed and suggestions for further research are provided.
Keywords: Magneti Marelli; fuzzy logic; fuzzy triangular numbers; R&D assessment; PERFORMANCE INDICATORS